Human milk fatty acid composition is associated with dietary, genetic, sociodemographic, and environmental factors in the CHILD Cohort Study. Issue 6 (7th October 2019) - Miliku, Kozeta; Duan, Qing Ling; Moraes, Theo J; Becker, Allan B; Mandhane, Piushkumar J; Turvey, Stuart E; Lefebvre, Diana L; Sears, Malcolm R; Subbarao, Padmaja; Field, Catherine J; Azad, Meghan B
ABSTRACT: Background: Fatty acids are a vital component of human milk. They influence infant neurodevelopment and immune function, and they provide ∼50% of milk's energy content. Objectives: The objectives of this study were to characterize the composition of human milk fatty acids in a large Canadian birth cohort and identify factors influencing their variability. Methods: In a subset of the CHILD cohort ( n = 1094), we analyzed milk fatty acids at 3–4 mo postpartum using GLC. Individual and total SFAs, MUFAs, and n–3 and n–6 PUFAs were analyzed using SD scores and principal component analysis (PCA). Maternal diet, sociodemographic, health, and environmental factors were self-reported. Single-nucleotide polymorphisms were assessed in the fatty acid desaturase 1 ( FADS1-rs174556 ) and 2 ( FADS2-rs174575 ) genes. Results: Fatty acid profiles were variable, with individual fatty acid proportions varying from 2- to >30-fold between women. Using PCA, we identified 4 milk fatty acid patterns: "MUFA and low SFA, " "high n–6 PUFA, " "high n–3 PUFA, " and "high medium-chain fatty acids." In multivariable-adjusted analyses, fish oil supplementation and fatty cold water fish intake were positively associated with DHA and the "high n–3 PUFA" pattern. Mothers carrying the minor allele of FADS1-rs174556 had lower proportions of arachidonic acid (ARA; 20:4n–6). Independent of selected dietary variables and genetic variants, Asian ethnicity was associated with higher linoleic acid (18:2n–6) and total n–3 PUFAs. Ethnic differences in ARA were explained by FADS1 genotype. Maternal obesity was independently associated with higher total SFAs, the "high medium-chain fatty acid" pattern, and lower total MUFAs. Lactation stage, season, study site, and maternal education were also independently associated with some milk fatty acids. No associations were observed for maternal age, parity, delivery mode, or infant sex. Conclusions: This study provides unique insights about the "normal" variation in the composition of human milk fatty acids and the contributing dietary, genetic, sociodemographic, health, and environmental factors. Further research is required to assess implications for infant health.